Saliva secretion difference before and after rinsing with baking soda on menopause women - Anggraeni, Dewi; Tjahajawati, Sri; Wihardja, Rosiliwati (Universitas Padjadjaran, 2007)
Menopause women can experience a decrease in saliva secretion (decrease). To understand the clear picture about saliva secretion, the volume, flow rate, pH and viscosity were then measured. The aim of this research was to obtain a picture about the difference of saliva secretion before and after rinsing with baking soda on menopause women. The type of the research used was a laboratory quasi-experiment with comparative descriptive form. The technique used in this research is the survey method, and samples were taken using the multistage cluster random sampling method, and t-student statistical analysis. This research was conducted with the saliva collected with spitting method on 45 menopause women. The results show that the average volume, flow rate, pH and viscosity before rinsing with baking soda was 1.79 ml, 0.18 ml/minute, 7.40 and 0.81 mm2/second. The average volume, flow rate, pH and viscosity after rinsing with baking soda were 2.66 ml; 0.27 ml/minute; 8.67 and 0.78 mm2/second. Statistical analysis t-student on α = 0.05 shows volume changes, flow rate, pH and saliva viscosity before and after rinsing with baking soda was 0.873; 0.086; 1.273 and 0.037 respectively. The conclusion shows a significant difference between saliva secretion before and after rinsing with baking soda, and saliva secretion after rinsing with baking soda on menopause women.